2015
DOI: 10.1117/1.jmi.2.4.044501
|View full text |Cite
|
Sign up to set email alerts
|

Light source design for spectral tuning in biomedical imaging

Abstract: We propose an architecture with a remote phosphor-based modular and compact light-emitting diode (LED) light source in a noncontact dermoscope prototype for skin cancer screening. The spectrum and color temperature of the output light can easily and significantly be changed depending on spectral absorption characteristics of the tissues being imaged. The new system has several advantages compared to state-of-the-art phosphor converted ultrabright white LEDs, used in a wide range of medical imaging devices, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…Basu et al . 4 found that lower CCTs enhanced contrast between melanin and hemoglobin when diagnosing skin cancer. Wang et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Basu et al . 4 found that lower CCTs enhanced contrast between melanin and hemoglobin when diagnosing skin cancer. Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…The trends in ÁE ab performance suggest that specific colour differences may be enhanced by different CCTs. Basu et al 4 found that lower CCTs enhanced contrast between melanin and hemoglobin when diagnosing skin cancer. Wang et al 3 found that CCTs in the range of 4000 to 5000 K were optimal for maximising colour difference in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is more important to ensure comparable colors in every picture taken by the system. The light source and image algorithms can further be improved by spectral tuning to enhance visibility of different features relevant for diagnostics in dermatology [26].…”
Section: Discussionmentioning
confidence: 99%
“…Adjustment of white and colorful emission from both organic and inorganic materials is often required for use in displays, [1][2][3] superbright solid-state lighting, 4 imaging 5 , anti-counterfeiting, 6,7 fluorescence labeling for bio-imaging, 8 chemosensors, 9 environmentally friendly 10 and biomedical applications. 11,12 In the topic of displays, newer materials and their combinations are pursued to provide bright and saturated colors, high energy efficiency, and excellent contrast. It is worth distinguishing the approach presented in Angewandte Chemie.…”
Section: Jaroslaw Mysliwiecmentioning
confidence: 99%